Proximate neutral lipid composition of niger (Guizotia abyssinica Cass.) seed - Mohamed Fawzy Ramadan; Jörg-Thomas Mörsel (Czech Journal of Food Sciences, 2002)
Niger (Guizotia abyssinica Cass.) seed was extracted with hexane (H) and chloroform/methanol (CM) (2:1, v/v) to determine the effect of the solvent on the amount and composition of the recovered lipid. The amount of the total lipid (TL) extracted with H was 29.6% of the seed weight, while that extracted with CM was 49.9%. Column and thin-layer chromatographic procedures on Silica Gel were performed to fractionate the main neutral lipid (NL) subclasses. Fatty acid composition of the NL subclasses, triacylglycerol (TAG) molecular species, and sterol (ST) content were estimated. The NL amount was found to be higher (97% of TL) in the H extract than in the CM extract (93% of TL). TAG appeared to be the predominant NL subclass (89.7-91.9% of total NL). Linoleic acid (C18:2n-6) was the main fatty acid followed by oleic acid (C18:1n-9) as the second main unsaturated fatty acid, while palmitic acid (C16:0) was the major saturated fatty acid. With high temperature gas-liquid chromatography using a flame ionization detector (HTGLC/FID) and H2 as the carrier gas, the actual TAG molecular species according to their carbon numbers were separated. TAG of even carbon numbers 16 and 18 were contained in six TAG molecular species. The major peaks occured at C54:6, and C54:3 corresponding to trilinolein and triolein. Furthermore, TAG molecular specie, expected to contain two molecules of linoleic acid (C54:5), was detected in a high level. Phytosterol pattern was determined without derivatization in the unsaponifiable fractions by HTGLC/FID. ST profile was characterized by a high total amount accounting for 4.22 g/kg of total H extract, and 4.00 g/kg of total CM extract. b-Sitosterol (2.035-1.929 g/kg TL) was the main component in both extracts. The major ST found were, in order of decreasing prevalence, b-sitosterol > campesterol > stigmasterol > D5-ave-nasterol > D7-avenasterol > lanosterol.